A Molecularly Defined Medullary Network for Control of Respiratory Homeostasis - Tianjiao Deng; Xinyi Jing; Liuqi Shao; Yakun Wang; Congrui Fu; Hongxiao Yu; Xiaoyi Wang; Xue Zhao; Fanrao Kong; Yake Ji; Xiaochen Tian; Wei He; et al. (Advanced Science)
Abstract The dynamic interaction between central respiratory chemoreceptors and the respiratory central pattern generator constitutes a critical homeostatic axis for stabilizing breathing rhythm and pattern, yet its circuit‐level organization remains poorly characterized. Here, the functional connectivity between two key medullary hubs: the nucleus tractus solitarius (NTS) and the preBötzinger complex (preBötC) are systematically investigated. These findings delineate a medullary network primarily comprising Phox2b‐expressing NTS neurons (NTSPhox2b), GABAergic NTS neurons (NTSGABA), and somatostatin (SST)‐expressing preBötC neurons (preBötCSST). Photostimulation of NTSPhox2b neurons projecting to the preBötC potently amplifies baseline ventilation, whereas genetic ablation of these neurons or knockout of their transient receptor potential channel 5 (TRPC5) significantly blunts the CO2‐stimulated ventilatory responses. Conversely, NTSGABA neuron stimulation inhibits or halts breathing partially via monosynaptic inhibition of NTSPhox2b neurons projecting to the preBötC. Additionally, photostimulation of preBötCSST neurons projecting to the NTS drives deep and slow breathing through coordinated modulation of NTSGABA and NTSPhox2b neurons. These findings collectively identify an important medullary network that integrates chemosensory feedback with respiratory motor output, enabling dynamic tuning of breathing patterns to metabolic demands.